The Development of Science Learning Video Media to Increase Elementary School Students' Interest in Learning - Tridays Repelita; Tia Latifatu Sadiah; Depi Prihamdan (Postgraduate, University of Mataram, 2023)
This study aims to develop based learning video for students of interest learning in class IV SDN Karawang Kulon 1 Kab. Karawang. The main data from this study are (a) knowing the facilities owned by the school based on the results of interviews with the Principal, (b) the teaching media used by the teacher during learning based on interviews with classroom teachers, (c) the interest in learning that students have based on observations in the classroom when learning takes place. This research uses research and development (R&D) methods. The development model used is the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). These results showed that (a) the facilities owned by the school could be used properly, and (b) the developed media were feasible to use in class, this was seen from the results of 98% media expert validation and 96.2% material expert validation with very feasible categories (c) student learning interest increases when learning uses video learning media, this is seen from the results of the N-Gain Test of 0.7 in the high category.